Analysis of Passive Line Impedance Stabilization Network Filter to Reduce Harmonics at DC- DC Converter - monica tri buana putri (CYCLOTRON, 2026)
The study aimed to develop a passive LISN filter capable of reducing total harmonic distortion of current (THDi) and voltage (THDv) in a DC-DC converter system, and to evaluate its effectiveness in improving overall system efficiency. The focus of this review is to assess the methodology, results, strengths, and weaknesses of the study in the context of recent literature on harmonic mitigation and EMI/EMC techniques in power electronic systems. Additional literature is also reviewed concerning input filter design, LISN characteristics, and EMI mitigation in power converters. Through an experimental approach, the study demonstrated a reduction of THDi by 25–30% and THDv by about 0.5%, although the results did not fully meet the IEEE 519-1992 harmonic standards. This review compares those findings with recent works on input filter design, harmonic mitigation methods, and LISN applications for electromagnetic compatibility (EMC). The analysis concludes that a passive LISN filter is effective as an initial stage for harmonic mitigation but requires a more complex (multi-stage or hybrid active-passive) design for optimal attenuation and better stability against variations in grid impedance.